2021
DOI: 10.1371/journal.pone.0260693
|View full text |Cite
|
Sign up to set email alerts
|

The impacts on food purchases and tax revenues of a tax based on Chile’s nutrient profiling model

Abstract: Background In June 2016, Chile implemented the Law of Food Labelling and Advertising, which included a mandatory front-of-pack warning labels on food and beverages high in added sugar, saturated fat, sodium or energy density, restrictions on child-directed marketing and on the promotion and sales of these products in schools. The regulation does not include taxes although Chile had implemented a tiered tax on SSBs two years before this law was implemented. Therefore, the objective of the study was to simulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…In addition to fiscal measures, non-fiscal measures are equally important. While the majority of past studies have shown a negative relationship between health taxes and unhealthy consumption or NCD prevalence (70,(75)(76)(77)(78)(79)(80), anticipating consumers' substitution with cheaper but equally harmful alternatives is important (68,81). Therefore, increasing consumer awareness to consciously limit their consumption of unhealthy products should be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to fiscal measures, non-fiscal measures are equally important. While the majority of past studies have shown a negative relationship between health taxes and unhealthy consumption or NCD prevalence (70,(75)(76)(77)(78)(79)(80), anticipating consumers' substitution with cheaper but equally harmful alternatives is important (68,81). Therefore, increasing consumer awareness to consciously limit their consumption of unhealthy products should be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…9 10 Finally, we assessed the potential impact of redesigning taxes as a stand-alone intervention; however, recent evidence from Chile shows that coupling taxes with front-of-package warning labels and regulation of food and beverages offered in schools, could lead to larger gains. 32 We acknowledge that we lack comprehensive uncertainty intervals for our estimates because we could not obtain CIs or SEs for price elasticities and obesity BMJ Global Health costs-not reported in the papers used-and for job losses as the input-output matrix provides point estimates only. Thus, our CIs underestimate the uncertainty associated with all of these data sources and should be interpreted cautiously.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…There is ongoing discussion around furthering policy integration efforts by linking the tax designs in Chile with its Food Labeling and Marketing Law. Simulations of expanding the tax to include unhealthy processed foods in Chile show that with such a tax, in line with food labeling and marketing regulations, household purchases of these items would fall dramatically (Caro et al 2017;Colchero, Paraje, and Popkin 2020). In addition, there would be reductions in nutrients of concern in Chile (sugar, sodium, saturated fats, and calories) linked with the most common NCDs (Caro et al 2017).…”
Section: Chilementioning
confidence: 99%